Meningkatkan Promosi UMKM Jasa Dengan Penerapan Digital Marketing dan Kontrol Biaya Melalui Pembukuan - Nurhayati Haviyyan; Nugraeni Nugraeni (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The rapid development of digital technology requires Micro, Small, and Medium Enterprises (MSMEs) to adapt by utilizing digital marketing and improving financial management practices. However, many service-based MSMEs have not yet optimized digital promotion and integrated bookkeeping in their business operations. This community service activity aims to enhance the promotion of service MSMEs through the implementation of digital marketing and to strengthen cost control through simple bookkeeping at AND CUSTOM LED. The methods used include an initial survey, practical mentoring, and evaluation of the activities. The mentoring process involved training in promotional content creation, the use of social media as a business communication tool, and the application of daily transaction recording. The results indicate an improvement in the business owner’s understanding and behavior regarding promotional management and financial recording. The MSME owner became more active and consistent in implementing digital promotion strategies and more disciplined in recording income and expenses. In addition, the mentoring encouraged a more independent and well-planned work attitude. Overall, this activity demonstrates that integrating digital marketing with simple bookkeeping can improve the quality of service MSME management and support business sustainability in the digital era.